Pedagogical and accessibility guidelines for open educational resources focusing on blind students - Soares, Michele dos Santos; Kakinohana, Gustavo Kikey; Cagnin, Maria Istela; Silva, Kennedy dos Santos; Fontão, Awdren de Lima; Freire, André Pimenta; Paiva, Débora Maria Barroso (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Open Educational Resources (OER) are gaining an increasingly significant space, as they provide new ways of learning, make it possible to work on content in an interdisciplinary way and allow improving and adapting content. However, although OER can support the teaching-learning process and benefit all parts of the educational system, blind students still encounter several factors that hinder or impede access to computer systems and face many accessibility problems, such as images no description, buttons without labels or texts in image format. Therefore, this paper aims to present a set of pedagogical and accessibility guidelines for OER focusing on addressing the needs of students who are blind. The recommendations were created based on bibliographical research and responses to a questionnaire submitted to blind students, in which it was possible to detect the main accessibility barriers and discover the difficulties they face. Finally, these guidelines were evaluated by a group of experts in accessibility and pedagogy using the peer review technique. The results showed that the guidelines meet both pedagogical and accessibility characteristics and are useful for building accessible OER.